Decision Support System Model for Determining Priority Criteria for Quality of DANA Application Services Using the AHP Method - Riko Amanah Gusni; Rieska Rahayu Ayuningsih; Rahmat Hidayat (Ali Institute or Research and Publication, 2026)
Amid the rapid adoption of financial technology in Indonesia, user satisfaction has become a critical factor in sustaining digital wallet services. This study aims to analyze and determine the priority of service quality criteria that most significantly influence user satisfaction with the DANA application, while also developing a Decision Support System (DSS) model based on the Analytical Hierarchy Process (AHP) method to assist developers and product management in establishing service improvement priorities. This study employs a descriptive quantitative approach involving 152 students from the Information Systems Study Program at Universitas Nusa Putra, selected using a purposive sampling technique. Primary data were collected through a pairwise comparison questionnaire to assess four main dimensions of service quality: Security, Ease of Use, Performance, and Features. The AHP method was applied to generate priority weights for each criterion and to evaluate the consistency of respondents’ judgments. The analysis results indicate that Security is the top priority with a weight of 44.8%, followed by Ease of Use (25.1%), Performance (17.9%), and Features (12.2%). The Consistency Ratio (CR) value of 0.076 (< 0.1) confirms that the respondents’ judgments are consistent and valid. These findings demonstrate that for users with high technological literacy, data protection and usability are prioritized over feature completeness. The proposed DSS model provides a systematic decision-making framework for developers to focus on strengthening cybersecurity measures and simplifying the user interface to maintain user trust and loyalty.